Osteoblastoma of the Lateral Skull Base: Work-Up, Surgical Management, and a Review of the Literature” - Miller, Craig; Khan, Rihan; Lemole, G. Michael, Jr.; Jacob, Abraham (Journal of Neurological Surgery Reports, 2013)
Objectives To describe the work-up and surgical management of an osteoblastoma involving the lateral skull base. Typically occurring in the spine or long bones, osteoblastomas of the craniofacial skeleton are exceedingly rare and infrequently reported. A review of the current literature regarding temporal bone osteoblastoma, diagnosis, and treatment is described.Methods This case report describes the clinical presentation, radiographic studies, surgical management, histology, and postoperative follow-up of a young man presenting to a tertiary care neurotology practice with osteoblastoma involving the lateral skull base. A review of the current literature regarding osteoblastoma of the skull base, work-up, and treatment is described.Results A 15-year-old adolescent boy with a greater than 1-year history of right-sided retroauricular pain, a palpable postauricular mass, and chronic headaches presented for evaluation/management. Microscope examination of the ears, hearing, and cranial nerve function were normal. High-resolution temporal bone computed tomography and magnetic resonance imaging scans were obtained, which revealed an expansile mass involving the junction of the temporal and occipital bones. The patient underwent a combined retrosigmoid/retrolabyrinthine resection of this extradural tumor. Histology revealed a benign bone neoplasm consistent with osteoblastoma. Complete surgical resection was achieved, and the patient's symptoms fully resolved. Follow-up imaging studies found no evidence of recurrence. The scientific literature relevant to work-up and management of osteoblastoma is reviewed.Discussion Osteoblastomas of the lateral skull base are rare, histologically benign tumors that can present with radiographic features suggestive of malignancy. An en bloc resection is important for both diagnosis and definitive treatment of these neoplasms. The differential diagnosis on imaging and histology is discussed.
Keywords: osteoblastoma; temporal bone; lateral skull base; retrosigmoid; retrolabyrinthine